Natural History and Malignant Transformation in Recurrent Respiratory Papillomatosis: Human Papillomavirus (HPV), Dysplasia and an Autopsy Review. (1st April 2015) - Can, Nhu Thuy; Tretiakova, Maria S.; Taxy, Jerome B.
Abstract : Introduction: Recurrent respiratory papillomatosis (RRP) is a human papillomavirus (HPV) related disease in both children and adults, characterized by recurrent benign squamous papillomas of the respiratory mucosa. Malignant transformation is rare. The present report concerns the natural history of RRP in two children. Materials and Methods: Clinical records, autopsy material and tissue from previous surgical excisions were reviewed in both cases. Select surgical and autopsy specimens were examined using p16 immunohistochemistry and in-situ hybridization for low and high risk HPV. Results: Both children had pulmonary involvement with incidental invasive keratinizing squamous carcinoma of the lung at autopsy. Low-risk HPV was present in the papillomas and carcinoma at autopsy in both cases. Conclusions: The autopsy examinations in these two cases emphasize the serious, if uncommon, pulmonary complications of this disease. In conjunction with previously reported autopsies, destructive lung disease may be as frequent a cause of death as disseminated malignancy.